Exploring Effective Pedagogies in Environmental and Sustainability Education for Teachers: A Story of New Zealand Pre-Service Teachers’ Learning Experiences - Sally Birdsall (Brock Education: a Journal of Educational Research and Practice, 2022)
Although teachers have been identified as key change agents in the shift towards a flourishing planet for all, research into effective pedagogies for embedding environmental and sustainability education (ESE) into teacher education courses is an emerging area. Understandings about the most effective approaches and activities are needed, along with theories that could underpin teachers’ learning. This study explores 21 pre-service primary school teachers’ learning following their engagement in an elective course designed to help them embed ESE into their future practice. Qualitative data were gathered using reflections as well as peer and individual interviews. An analysis showed that the activities considered most valuable for learning were those that gave pre-service teachers space and time to think more deeply and in different ways. Mezirow’s transformative learning theory was used to explore their learning. The use of its three elements and six components identified that transformative learning took place for about half of these pre-service teachers. While it seems this theory has potential to underpin ESE teacher education courses, further research is needed to explore how transformation can occur for more teachers.